2017
DOI: 10.1021/acs.jpca.7b06447
|View full text |Cite
|
Sign up to set email alerts
|

In Quest of the Alanine R3 Radical: Multivariate EPR Spectral Analyses of X-Irradiated Alanine in the Solid State

Abstract: The amino acid l-α-alanine is the most commonly used material for solid-state electron paramagnetic resonance (EPR) dosimetry, due to the formation of highly stable radicals upon irradiation, with yields proportional to the radiation dose. Two major alanine radical components designated R1 and R2 have previously been uniquely characterized from EPR and electron-nuclear double resonance (ENDOR) studies as well as from quantum chemical calculations. There is also convincing experimental evidence of a third minor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Many studies on the composition of the alanine EPR spectrum are available in the literature [ 32 , 33 , 34 , 35 ]. It has been shown that the EPR spectrum of irradiated alanine consists of at least three different radical species [ 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies on the composition of the alanine EPR spectrum are available in the literature [ 32 , 33 , 34 , 35 ]. It has been shown that the EPR spectrum of irradiated alanine consists of at least three different radical species [ 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…9 Its spectrum was only recently isolated in a statistical decomposition study of the EPR spectrum. 11 In more fortunate cases, for example, when the EPR components of minority species are narrow and easier to distinguish, better sensitivity could be expected.…”
Section: Discussionmentioning
confidence: 99%
“…It has to be noted, however, that the aforementioned radical was difficult to characterize even in single crystals due to the weakness of its relative contribution (<10%) and the simultaneous presence of several conformations . Its spectrum was only recently isolated in a statistical decomposition study of the EPR spectrum . In more fortunate cases, for example, when the EPR components of minority species are narrow and easier to distinguish, better sensitivity could be expected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations